The type, amount, frequency and timing of dietary supplement use by elite players in the First Spanish Basketball League - Schröder, H.; Navarro, E.; Mora, J.; Seco, J.; Torregrosa, J. M.; Tramullas, A. (Journal of Sports Sciences, 2002)
The aims of this study were to determine the type, frequency and amount of dietary supplement consumption among a group of professional basketball players. The type, amount and specific timing of supplement use were recorded by 55 professional basketball players from seven different teams of the First Spanish Basketball League. Most participants (58%) consumed dietary supplements. Multivitamins and vitamins were the most frequently used supplements among the athletes (50.9%), followed by sport drinks (21.8%), miscellaneous supplements (21.8%), amino acids (14.5%), proteins (12.7%) and carbohydrates (12.7%). The average daily dietary supplement was one capsule of multivitamins, one capsule of antioxidant vitamins, 0.2-1.0 g vitamin C, 10.3 g protein, 1.9 g amino acids, 16.2 g carbohydrates and 377 ml of a commercial sport drink. Although the proportion of participants who consumed dietary supplements before, during and immediately after exercise was 25.4%, 16.3% and 7.3% respectively, only a few consumed a potentially ergogenic supplement at these times. It would appear unlikely that the type or amount of dietary supplements consumed had a beneficial effect on the physical performance of these professional basketball players, with the possible exception of antioxidant vitamins and the commercial sport drinks.